Metabolic Controls on Epigenetic Reprogramming in Regulatory T Cells - Lu, Jingli; Liang, Yan; Meng, Haiyang; Zhang, Ailing; Zhao, Junjie; Zhang, Chengliang (Frontiers in Immunology, 2021)
Forkhead box protein 3 (Foxp3+)-expressing regulatory T (Treg) cells are a unique CD4+T cell subset that suppresses excessive immune responses. The epigenetic plasticity and metabolic traits of Treg cells are crucial for the acquisition of their phenotypic and functional characteristics. Therefore, alterations to the epigenetics and metabolism affect Treg cell development and function. Recent evidence reveals that altering the metabolic pathways and generation of metabolites can regulate the epigenetics of Treg cells. Specifically, some intermediates of cell metabolism can directly act as substrates or cofactors of epigenetic-modifying enzymes. Here, we describe the metabolic and epigenetic features during Treg cell development, and discuss how metabolites can contribute to epigenetic alterations of Treg cells, which affects Treg cell activation, differentiation, and function.